Effects of Multicultural Education on Small Presses and Commercial Publishing: A Case Study of the House on Mango Street. - Layfield, Allison (Children's Literature in Education, 2021)
During the 1980s and 1990s, the multicultural education movement in the United States aimed to educate diverse students about a diverse United States. While the effects of multicultural education are often discussed in terms of its curriculum and effects on students, the movement's effects on the publishing system have been overlooked. This article argues that the multicultural education movement made an impact on diversity in publishing through (a) identifying transformative texts at the cusp of activist movements, (b) successfully arguing for a text's classroom inclusion by appealing to critics and supporters of multicultural education, and (c) insisting on culturally accurate books by and about people of color, which led to a shift in the relationships between large commercial publishers and small, activist presses. This article outlines the impact of this process on Latinx literature through a case study of The House on Mango Street by Sandra Cisneros. In doing so, this article shifts the discussion about multicultural education as a pedagogical tool to an examination of its cultural effects beyond education and makes recommendations for new methods educators can use to influence the publishing and distribution of diverse literature for young people.